HUBUNGAN ANTARA PENGETAHUAN GIZI DAN MOTIVASI BELAJAR DENGAN KREATIVITAS SISWA DALAM MENGOLAH MAKANAN - Hastowati, Sri Kawuryan (Pusat Data dan Teknologi Informasi Kementerian Pendidikan Kebudayaan, Riset dan Teknologi, 2005)
// Â The objective of the research is to study correlation between knowledge of nutrition and learning motivation with student creativity in a food process. The research carried out at Public Senior Vocational School (SMKN) in Jakarta, with 90 respondents selected by using cluster random sampling. The research concludes that there are positive correlation between knowledge of nutrition with student creativity in a food process, with ry1 = .728 and 1 499.4316.91Ë† XY ï€«ï€½ , and there is a positive correlation between learning motivation withÂ student creativity in a food process, with ry2 =.863Â and Y Ë† =25.021+ 1.516X2. Furthermore, there is a positive correlation between those two independent variables with student creativity in a food process, with Ry.12 = .971 and =5.354+1.559X1+ 1.543X2.// //